Chromosome and gene copy number variation allow major structural change between species and strains of Leishmania - Rogers, Matthew B.; Hilley, James D.; Dickens, Nicholas J.; Wilkes, Jon; Bates, Paul A.; Depledge, Daniel P.; Harris, David; Her, Yerim; Herzyk, Pawel; Imamura, Hideo; Otto, Thomas D.; Sanders, Mandy; et al.

(untitled) (Genome Research, 2011)
Leishmania parasites cause a spectrum of clinical pathology in humans ranging from disfiguring cutaneous lesions to fatal visceral leishmaniasis. We have generated a reference genome for Leishmania mexicana and refined the reference genomes for Leishmania major, Leishmania infantum, and Leishmania braziliensis. This has allowed the identification of a remarkably low number of genes or paralog groups (2, 14, 19, and 67, respectively) unique to one species. These were found to be conserved in additional isolates of the same species. We have predicted allelic variation and find that in these isolates, L. major and L. infantum have a surprisingly low number of predicted heterozygous SNPs compared with L. braziliensis and L. mexicana. We used short read coverage to infer ploidy and gene copy numbers, identifying large copy number variations between species, with 200 tandem gene arrays in L. major and 132 in L. mexicana. Chromosome copy number also varied significantly between species, with nine supernumerary chromosomes in L. infantum, four in L. mexicana, two in L. braziliensis, and one in L. major. A significant bias against gene arrays on supernumerary chromosomes was shown to exist, indicating that duplication events occur more frequently on disomic chromosomes. Taken together, our data demonstrate that there is little variation in unique gene content across Leishmania species, but large-scale genetic heterogeneity can result through gene amplification on disomic chromosomes and variation in chromosome number. Increased gene copy number due to chromosome amplification may contribute to alterations in gene expression in response to environmental conditions in the host, providing a genetic basis for disease tropism.